1992
DOI: 10.1079/bjn19920043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amount of dietary fat and protein on esterase-1 (ES-1) activities of plasma and small intestine in rats

Abstract: The objective of the present study was to characterize nutritionally esterase-1 (ES-1). For this purpose, the effects of replacement of dietary carbohydrates by isoenergetic amounts of either fat or protein on ES-1 activities of plasma and small intestine were studied in male rats. Purified diets differing in the amounts of maize starch plus dextrose, casein and various types of fat were used. Plasma and jejunal ES-1 activities were found to be increased with increasing fat intakes. As to the type of fat, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The magnitude of the esterase activities appears to be related to Fa metabolism. For example, a chronic intake of unsaturated fatty acids (UFa)-rich diets, such as omega-3 (linolenic acid) and omega-6 (linoleic acid) induced a rise in intestinal esterase activity in rats (Van lith et al 1992). a comparative study conducted on fifty-five species of free-living birds belonging to eight orders revealed that passerines with wider dietary diversity (i.e., mixed diets) had the highest hydrolytic activity of liver esterase amongst all birds assessed (Bush et al 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the esterase activities appears to be related to Fa metabolism. For example, a chronic intake of unsaturated fatty acids (UFa)-rich diets, such as omega-3 (linolenic acid) and omega-6 (linoleic acid) induced a rise in intestinal esterase activity in rats (Van lith et al 1992). a comparative study conducted on fifty-five species of free-living birds belonging to eight orders revealed that passerines with wider dietary diversity (i.e., mixed diets) had the highest hydrolytic activity of liver esterase amongst all birds assessed (Bush et al 1973).…”
Section: Introductionmentioning
confidence: 99%